The impact of firm subsidies: Evaluating German regional policy - Bastian Alm; Franz-Josef Bade (Technische Universität Dortmund, 2009)
Recently, the number of state interventions and of firm subsidies has largely increased. However, the possible outcome of such interventions is rather am-biguous. This paper investigates the impact of firm subsidies granted by Ger-man regional policy. The long experiences made with regional capital and em-ployment assistances provide a good opportunity for evaluating the impact of firm subsidies in a systematic way. The first part of the paper begins with a brief introduction into the institutional structure of the German regional assis-tance scheme, its objectives and main instruments. It follows a discussion of earlier evaluation studies putting the emphasis on their methodological charac-teristics. In the second part, an alternative approach of impact analysis is devel-oped concentrating on the economic performance of the individual firm as-sisted by investment grants. The empirical basis is given by linking data of the assisted firms with the social security data differentiated by firms. One main advantage of the uniform database is that it allows to measure and to compare the employment performance of assisted and non-assisted firms free of distor-tions caused by different data sources. In addition, the database provides in-formation about the number and structure of firm employment for a longer pe-riod of time. Thus, micro-econometric methods of evaluation are applied such as matching procedures by pairing firms with and without financial subsidies and controlling them for other influences, simultaneously.
Additional information: Paper presented at 56th North American Meetings of the Regional Science Association
Keywords: C14; R00; R11; C21; R28; R58; 330; Policy Evaluation; Regional Policy; Capital Subsidies; Statistical Matching